Effect of Superoxide Dismutase (SOD) Supplementation on Plasma Levels of Malondialdehyde (MDA), Total Cholesterol and LDL Cholesterol in the Elderly - Dwi Ngestiningsih; Rejeki Andayani Rahayu; Lusiana Batubara (Journal of Biomedicine and Translational Research, 2019)
Background: Several various physiological functions in elderly people are diminished due to cell or tissue damage. One of the probable causes are oxidative stress yielded by free radicals.Oxidative stress (ROS) induce lipid peroxidation in endothelial cell membrane, which generates atherosclerotic plaque. In a state of oxidative stress, MDA level will increased. The purpose of this study is to determine the effect of SOD supplementation on MDA, total cholesterol and LDL cholesterol plasma levels in the elderly.Methods: This study was open label, a randomized control trial. Subjects were elderly people aged > 60 years (median 75, 60-82 ys, male 10 (24,4%)) institutionalized at Social Rehabilitation Unit Pucang Gading Semarang, Indonesia. The treatment group consisted of 16 people, received SOD (GlisodinR) 1 capsule (250 IU) 1 hour before meals, plus exercise scheduled for 8 weeks. The control group consisted of 15 people, received placebo, and exercise. Plasma MDA levels were examined using TBARS method, while total cholesterol and LDL cholesterol were examined using CHOD-PAP method.Results: This study show a reduction of plasma MDA levels in the treatment group compare to control group ( p = 0.062 ). A significant reduction of total cholesterol and LDL cholesterol levels in the treatment group were found (before 190.00 and 131.47 g/dl, after 182.27 and 121.93 g/dl, p = 0.005 and 0.001).Conclusion: The SOD supplementation significantly reduce Total Cholesterol and LDL level, but not MDA level in the elderly.